Glycogen Storage Disease 1b: Diagnosis and Workup of a Novel Mutation - Sanjeev, Rama Krishna; Shetty, Swathi; Harith, Arun; Nair, Bindu T; Surendran, Sajith (Journal of Nepal Paediatric Society, 2016)
Glycogen Storage diseases (Glycogenoses) are a diverse group of disorders, numbering more than 12, resulting from deficiencies of various enzymes & transport proteins in the pathways of glycogen metabolism. GSD 1 is caused by absence or deficiency of glucose-6-phosphatase activity in the liver, kidney or intestinal mucosa. In GSD 1(b), the enzyme which transports Glucose-6-Phosphate across the microsomal membrane is defective, thereby resulting in accumulation of Glycogen. The clinical features of 1a & 1b are similar with fasting hypoglycaemia, hepatomegaly, growth retardation and metabolic abnormalities except for the presence of neutropenia with recurrent gingivitis in GSD 1b. A genetic diagnosis solves this conundrum with the added benefit of antenatal diagnosis of future pregnancies & identification of carrier state in patients. We report the work up of an infant with suspected GSD where a novel mutation with heterozygous carrier state in the parents was diagnosed by genetic testing. J Nepal Paediatr Soc 2016;36(1):85-87.